2023
DOI: 10.3390/horticulturae9060725
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nano Chito Oligomer Hybrid Solution for the Treatment of Citrus Greening Disease (CGD) and Biostimulants in Citrus Horticulture

Abstract: Citrus greening disease (CGD), or Huanglongbing (HLB), is principal in Citrus farming because of its severe damage, decreased yield, poor quality of fruit, and frequent disappearance before harvest. Present research blended silver nanoparticles (AgNPs) colloid with chitooligomers and monomers (COAMs) to create the composites referred to as a “hybrid solution”. The hybrid solution has been synthesized for antimicrobial effects and plant growth stimulation. The hybrid solution was applied to cure the CGD, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…It is not known yet if there may be a significant diffusion and translocation of the AgNPs from the leaf to the root. Some studies report that AgNPs may act as a bio-stimulant that enhances the plant defence mechanisms against fungal infections [28][29][30].…”
Section: In Vivo Interaction Assay Of Agnps Against Fusariummentioning
confidence: 99%
“…It is not known yet if there may be a significant diffusion and translocation of the AgNPs from the leaf to the root. Some studies report that AgNPs may act as a bio-stimulant that enhances the plant defence mechanisms against fungal infections [28][29][30].…”
Section: In Vivo Interaction Assay Of Agnps Against Fusariummentioning
confidence: 99%
“…Nanoparticles, especially silver nanoparticles, have garnered significant attention due to their unique properties and potential applications in various fields (Bhuyar et al, 2020;Vatcharakajon et al, 2023). However, conventional synthesis methods often employ toxic chemicals, raising environmental concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Silver-based antimicrobial materials have broad-spectrum antibacterial properties, but due to their high active surface area and easy oxidation, nano-silver is prone to aggregation and deactivation, thus reducing its antimicrobial effect [26]. Pakpoom et al [27] blended AgNP colloids with chitooligomers and monomers (COAMs) to create the composites and verified the synergistic antibacterial effects of AgNPs-COAMs. Omnia et al [28] prepared a new epoxy/chitosan-Ag nanocomposite coating and found that Ag and chitosan nanoparticles can improve the anticorrosion ability.…”
Section: Introductionmentioning
confidence: 99%